Prepositional noun phrases with adverbial meaning - Žele, Andreja (Slavia Centralis, 2023)
The article describes those prepositional phrases that have acquired, being constructed linguistic units and given their meanings and functions, the status of syntagms with adverbial meaning. The key element enabling a stable association of elements within prepositional phrases is the relation between a preposition and a noun, i.e. a co-dependence that operates on semantic, syntactic and formal levels. Within the prepositional phrase, the preposition plays the role of a dynamic or static connector, while the noun has the role of a substantive complement, which is defined as an adverbial clause. Therefore, this noun complement gives content to a dynamic or static prepositional morpheme, which is a preposition as a part of speech. The mutual connection and interdependence of the preposition and the noun, i.e. the colocability of the preposition and the noun, is measured by the available syntactic-semantic capabilities of the selected prepositions.
Keywords: prepositional phrase; preposition; noun; adverbial meaning; proposition